Improving Student Learning Creativity through Project Based Learning: A Systematic Literature Review - Putra, Ade Herdian (International Journal of Applied Counseling and Social Sciences, 2024)
Project Based Learning, also known with an acronym PjBL, has been acknowledged as a beneficial pedagogical approach to increase students' creativity in different areas of study. Existing literature regarding this learning approach and its repercussions on student innovation: a systematic review was conducted by this study. PjBL expands not only creative thinking abilities but motivation as well. Collaborative abilities are included, important inside the area of higher education, and also the realm of employment. Involvement in real-world tasks students actively can apply their gained knowledge to help real-world situations. Strengthening their cognizance as well as encouraging new thoughts, this experience does. However, project authenticity directly affecting its advancement should be ensured along with handling academic pressure within the PjBL method's successful implementation. Academic pressure at a high level can obstruct student creativity. A supportive learning atmosphere for mental health should be created accordingly. Such atmosphere needs students projects that maintains authenticity to boost enthusiasm and motivation. Integrating PjBL carefully within the curriculum. Participation of all related stakeholders: necessary for creation an atmosphere in educational establishments favors the fostering of creativity. This study gives new perspectives and practical suggestions to achieve efficient learning models. It highlights how crucial PjBL is, for empowering students to face challenges they encounter in future competences and jobs required, the importance.